Matlaʿu’ş-şems - Muhammed Hasan Han, 1843-1896. ([Tahran] Tahran, 1984)
3 cilt 2 ciltte (1. c. [41], 288 sayfa, 12 sayfa resim, 2. c. sayfa 289-790, [2] sayfa, [12] sayfa resim, tıpkıbasım ; 3. c. sayfa [12], 791-1441)